2021
DOI: 10.3390/ma14247830
|View full text |Cite
|
Sign up to set email alerts
|

From Blood to Bone—The Osteogenic Activity of L-PRF Membranes on the Ex Vivo Embryonic Chick Femur Development Model

Abstract: (1) Background: To evaluate the effects of the direct and indirect contact of leukocyte and platelet-rich fibrin (L-PRF) on bone development, in an ex vivo embryonic chick femur model. (2) Methods: Both sections of L-PRF membranes (red and yellow portions) were evaluated with scanning electron microscopy and histochemical staining. The in vivo angiogenic activity was evaluated using a chorioallantoic membrane model. The osteogenic activity was assessed with an organotypic culture of embryonic chick femora thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This technique allows a nondestructive 3D imaging and morphometric analysis of the bone tissue with a very high resolution. Attained datasets can be used to reconstruct the implant and neighboring bone tissue, further characterizing tissue parameters in a given region of interest [ 37 , 38 , 39 ]. This allows the feasible analysis of bone tissue 3D parameters (e.g., bone volume (BV), bone volume ratio (BV/TV)), and 2D parameters (e.g., bone surface (BS)).…”
Section: Resultsmentioning
confidence: 99%
“…This technique allows a nondestructive 3D imaging and morphometric analysis of the bone tissue with a very high resolution. Attained datasets can be used to reconstruct the implant and neighboring bone tissue, further characterizing tissue parameters in a given region of interest [ 37 , 38 , 39 ]. This allows the feasible analysis of bone tissue 3D parameters (e.g., bone volume (BV), bone volume ratio (BV/TV)), and 2D parameters (e.g., bone surface (BS)).…”
Section: Resultsmentioning
confidence: 99%
“…18 It has been used to characterize the bone tissue response in physiological and pathological experimental settings, as well as within the frame of distinctive bone healing therapeutic approaches. 19,23,[27][28][29][30] Nonetheless, to the best of the authors' knowledge, this model has not been previously characterized in the presence of bacterial infection, and neither have other all-bone organotypic tissue infection models been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The embryonic chick femur organotypic model is a reliable high‐throughput tool with rapid development that allows the characterization of distinct bone tissue‐related cell populations in the native environment, with the capability to respond translationally to a variety of stimuli 18 . It has been used to characterize the bone tissue response in physiological and pathological experimental settings, as well as within the frame of distinctive bone healing therapeutic approaches 19,23,27–30 . Nonetheless, to the best of the authors' knowledge, this model has not been previously characterized in the presence of bacterial infection, and neither have other all‐bone organotypic tissue infection models been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The culture conditions are quite simple involving only a standard culture medium without fetal bovine serum supplementation, as it is normally required for cell cultures, thus avoiding the differences in the batch and commercial sources, providing better correlation between studies. This ex vivo model has been used to address a large variety of bone-related setups [ 37 , 40 , 41 , 42 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, the research team reported the suitability of the embryonic chick femur model to address the osteogenic potential of MTA-based endodontic cements [ 37 ]. This system has proven to be a useful model in bone-related biology to address development, regeneration, and response to external stimuli [ 38 , 39 , 40 , 41 , 42 ]. In this model, 11th-day embryonic femurs were cultured ex vivo at the air/liquid interface.…”
Section: Introductionmentioning
confidence: 99%